2017
DOI: 10.1111/1750-3841.13741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Extrusion Parameters on Dietary Fiber in Wheat Bran and Rye Bran

Abstract: Wheat bran and rye bran are mostly used as animal feed today, but their high content of dietary fiber and bioactive components are beneficial to human health. Increased use of bran as food raw material could therefore be desirable. However, bran mainly contains unextractable dietary fiber and deteriorates the sensory properties of products. Processing by extrusion could increase the extractability of dietary fiber and increase the sensory qualities of bran products. Wheat bran and rye bran were therefore extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 47 publications
3
27
1
Order By: Relevance
“…On the contrary, Yan et al [21] observed an increase in the water-binding capacity of wheat bran after extrusion-cooking. Moreover, it was shown that dietary fibre was solubilised during extrusion-cooking [20][21][22] due to the conversion of water-unextractable arabinoxylan (WU-AX) to water-extractable arabinoxylan (WE-AX) and the release of β-glucan [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Yan et al [21] observed an increase in the water-binding capacity of wheat bran after extrusion-cooking. Moreover, it was shown that dietary fibre was solubilised during extrusion-cooking [20][21][22] due to the conversion of water-unextractable arabinoxylan (WU-AX) to water-extractable arabinoxylan (WE-AX) and the release of β-glucan [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The bran presents a high content of dietary fiber, vitamins, minerals, as well as phenolic compounds. The consumption of these compounds has been linked to important benefits in human health since they could help reduce the risk of suffering different diseases (Andersson, Andersson, Jonsäll, Andersson, & Fredriksson, 2017). Among the types of bran that can be used for the production of breakfast cereals are the oat-bran and wheat-bran.…”
Section: Introductionmentioning
confidence: 99%
“…Arabinoxylans Fermentation [102][103][104] Ultrasonic/microwave [105,106] Enzymatic treatment [107][108][109][110] Milling fractions [111][112][113] Alkaline treatment [114][115][116][117] Nixtamalization [118] Starch removal [119] Extrusion [80,86,89,120] Subcritical water treatment [119,121] β-glucans Ultrasound [122] Roller-milling/pearling [123] Milling [124][125][126] Fermentation [127,128] Enzymatic treatment [129,130] Extrusion [131][132][133][134] Subcritical water treatment [119,135,136]…”
Section: Compound Techniques Referencesmentioning
confidence: 99%